2014
DOI: 10.1186/bf03351730
|View full text |Cite
|
Sign up to set email alerts
|

Local time dependence of the dominant frequency of Pi2 pulsations at mid- and low-latitudes

Abstract: We carried out a statistical analysis of Pi2 pulsations using the geomagnetic field data obtained at three ground stations. A local time dependence of the dominant frequency of Pi2 was found on the nightside. The frequency of mid-latitude Pi2 pulsations is lower on the dusk side than that on the dawn side. This tendency is attributed to the shape of the plasmasphere which bulges out to the dusk side. It was confirmed that the Pi2 frequency depends also on the geomagnetic activity measured with Kp index. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 25 publications
7
35
0
Order By: Relevance
“…L = 1.2 ∼ 3.4), Kosaka et al (2002) found that the frequencies of Pi2 pulsations have local time dependence, that is, they are lower on the dusk side than those on the dawn side. Two stations they used were located in the southern hemisphere and the other one is in the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…L = 1.2 ∼ 3.4), Kosaka et al (2002) found that the frequencies of Pi2 pulsations have local time dependence, that is, they are lower on the dusk side than those on the dawn side. Two stations they used were located in the southern hemisphere and the other one is in the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…2. The start time of the 5-minute data set is generally taken at somewhere between the start time of 10-minute data set and the onset of the Pi2, which is nearly the same with that used by Kosaka et al (2002). The start time of the trailing-5-minute data set is defined as the time at 2 wavelengths after the onset, which is shown by the coarse dash line in upper panel of the Fig.…”
Section: Data Set and Event Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the same frequency was observed at both stations, THJ and KAK, and the observed frequency was lower than the expected frequency of the surface wave on the plasmapause (24 mHz $ ffiffi ffi 2 p times the FLR frequency at 0100 MLT) [Chen and Hasegawa, 1974]. A statistical study of surface mode Pi2 pulsations at midlatitudes and low latitudes showed also that the frequency $11 mHz is lower than the statistical result at 0100 MLT at Kp = 4 [Kosaka et al, 2002]. Thus the surface wave model is not appropriate for our Pi2 event.…”
Section: Mechanism For the Pi2 Pulsationmentioning
confidence: 89%